Double‐Torsion Measurements of the Brittle‐to‐Ductile Transition Temperature in Calcium Aluminosilicate Glasses. (8th March 2016) - Ferri, Luiz E.; Hoff, Kyle C.; Baker, Shefford P.
Abstract : While normally thought of as brittle, glass undergoes a brittle‐to‐ductile transition (BDT) as temperature increases and viscosity decreases. Understanding this transition is important both in glass manufacturing, particularly for thin sheet applications such as display glass, and in fundamental studies. A high‐temperature double‐torsion test apparatus has been developed and used to determine the BDT temperature of two commercial calcium aluminosilicate glasses. The BDT temperature can be found with high precision and compared with other characteristic temperatures such as the glass transition temperature or the softening point. The strain rate sensitivity of the BDT temperature is demonstrated.